Disparities in Cardiovascular Disease and Type 2 Diabetes Risk Factors in Blacks and Whites: Dissecting Racial Paradox of Metabolic Syndrome - Osei, Kwame; Gaillard, Trudy (Frontiers in Endocrinology, 2017)
Cardiovascular diseases (CVD) remain as the leading cause of mortality in the western world and have become a major health threat for developing countries. There are several risk factors that account for the CVD and the associated mortality. These include genetics, type 2 diabetes (T2DM), obesity, physical inactivity, hypertension, and abnormal lipids and lipoproteins. The constellation of these risk factors has been termed metabolic syndrome (MetS). MetS varies among racial and ethnic populations. Thus, race and ethnicity account for some of the differences in the MetS and the associated CVD and T2DM. Furthermore, the relationships among traditional metabolic parameters and CVD differ, especially when comparing black and white populations. In this regard, the greater CVD in blacks than whites have been partly attributed to other non-traditional CVD risk factors such as subclinical inflammation (C-reactive protein), homocysteine, increased LDL oxidation, lipoprotein a, adiponectin, and plasminogen activator inhibitor-1 (PAI-1), etc. Thus, to understand CVD and T2DM differences in blacks and whites with MetS, it is essential to explore the contributions of both traditional and nontraditional CVD and T2DM risk factors in blacks of African ancestry and whites of Europoid ancestry. Therefore, in this mini review, we propose that nontraditional risk factors should be integrated in defining MetS as a predictor of CVD and T2DM in blacks in the African diaspora in future studies.